(untitled) (Journal of Informatics Education and Research, 2025)
This study critically examines the effects of mentorship programs on job performance within the pharmaceutical and healthcare sectors industries characterized by high employee turnover and the need for skill-intensive labor. These sectors also grapple with increasing regulatory standards and rapid technological advancements, factors that heighten the demand for a highly skilled workforce. This research evaluates the influence of structured mentorship initiatives on job performance, focusing on skill development, professional confidence, and essential support for adapting to industry challenges. Using a sample of 85 professionals, the study utilizes statistical analyses in SPSS to determine the correlation between mentorship program participation and job performance metrics. Results underscore mentorship’s positive impact on key job performance areas, such as task proficiency, confidence, and adaptability. The findings highlight mentorship as a critical component in workforce development, suggesting that systematic implementation of mentorship could be instrumental in optimizing job performance and organizational resilience in these sectors.